Black spot mapping of University of the Philippines Diliman - Parco, John Michael E.
The study demonstrated a macroscopic analysis of traffic accidents through identification and mapping of black spots. This was applied in the vicinity of University of the Philippines-Diliman Campus by developing a user-friendly accident database spreadsheet application that can be used by its police department to summarize raw accident data in tabular form and automate Google Earth maps to help visualize the traffic accident situation of the campus. The necessary and existing accident data was obtained from the police department which is the authority in writing and keeping the traffic accident records. The spreadsheet application, which was enhanced in the Visual Basic for Applications (VBA) programming environment, provides the user to input data easily and has the function to automate KML codes that can be viewed in Google Earth. In this setup, the user is able to quickly transform raw data to maps which can be used by many GIS applications for further analysis. To test the application, accident spot maps were generated according to categories by year, casualty profile and type of locations. Using the classic statistical method, the black spots identified for both 90% and 95% confidence intervals were locations along Races Avenue corner Magsaysay Avenue and on the Bahay Ng Alumni Parking lot. The highest concentrations of accidents are in the parking lot of CSSP and Shopping Center for up to 99% confidence interval.